PENERAPAN PRINSIP GOOD GOVERNANCE DALAM PERATURAN PENGELOLAAN PERIKANAN YANG BERKELANJUTAN DI INDONESIA - Rizky Septiana Widyaningtyas (Penerbit Universitas Atma Jaya Yogyakarta, 2019)
This study aims to know and analyze and examine the realization of good governance principles in fisheries management regulation in Indonesia; analyze and formulate the ideal fisheries management regulation model in accordance with the concept of good governance.This research is normative juridical research, which is research that puts law as a building of norm system, consisting of principles, norms, rule of law, judgment, agreement, and doctrine. The approach used in this normative legal research is the statute approach and the conceptual approach. The data obtained were analyzed by qualitative method. Based on data analysis, it can be concluded that 1) Realization of 8 Main Characteristics of good governance according to UNESCAP are participation, orientation on consensus, accountable, transparent, responsive, effective and efficient, fair and inclusive and follow the rule of law in law, and efficient that cannot be applied; 2) The ideal fisheries management model in accordance with the principle of good governance is a co-management model, because this model use community empowerment and involve all stakeholders as well.